2022
DOI: 10.1109/lra.2022.3192637
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Designing a Lightweight and Energy-Efficient Kinematically Redundant Actuator

Abstract: Redundant actuators enable to distribute power among two motors, which can be selected optimally in terms of efficiency. We propose a methodology that finds effective combinations of motors and gearboxes for a dynamic load, taking into account the constraints, inertia, and efficiency of each component. Focusing on battery-operated robots as an application, it also considers battery pack mass in relation to the energy required by the actuator for multiple hours of operation. Based on this methodology, a prototy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In contrast, the dual motor actuator (DMA), depicted in Fig. 1, is a kinematically redundant actuator that has been explored in [21] and [23] extensively. This DMA comprises two motors, a differential, and an auxiliary gear set.…”
Section: Redundant Actuator Principles and Inertia Impact On Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the dual motor actuator (DMA), depicted in Fig. 1, is a kinematically redundant actuator that has been explored in [21] and [23] extensively. This DMA comprises two motors, a differential, and an auxiliary gear set.…”
Section: Redundant Actuator Principles and Inertia Impact On Selectionmentioning
confidence: 99%
“…Kinematically redundant actuators offer the potential to reduce energy consumption or provide a wider operating range than common actuators as discussed in detail in [21], and [22]. Additionally, we proposed a design methodology and selection of its components of the shelve to have a light and energy-efficient solution in [23]. In [24], researchers have demonstrated that the inertia of the actuator in certain working conditions is lower than the inertia of both drivetrains individuals.…”
Section: Introductionmentioning
confidence: 99%